The Effect of Antimicrobial Peptide (PA-13) on Escherichia coli Carrying Antibiotic-Resistant Genes Isolated from Boar Semen - Krittika Keeratikunakorn; Ratchaneewan Aunpad; Natharin Ngamwongsatit; Kampon Kaeoket (MDPI AG, 2024)
A major global public health concern is antimicrobial resistance (AMR). Antimicrobial peptides (AMPs) are a potentially appropriate replacement for conventional antibiotics. The purpose of this research was to investigate the potential of the antimicrobial peptide PA-13, a synthetic AMP with 13 amino acids, to inhibit E. coli isolated from boar semen expressing antibiotic-resistant genes, as well as to determine the mechanism of action of this antimicrobial peptide on the bacterial membrane. The effectiveness of the bacterial inhibitory activity of PA-13 was tested at different concentrations by two fold serial dilutions in the range 0.488-500 µg/mL using the MIC and MBC methods. The impact of PA-13 on the bacterial membrane was examined at different concentrations of 0×, 0.5×, 1×, 2× and 4× of MIC using DNA leakage assay and electron microscopy. The PA-13 antibacterial activity result exhibited the same MIC and MBC values at a concentration of 15.625 µg/mL. When comparing DNA leakage at different MIC values, the results revealed that the maximum amount of DNA concentration was found two and three hours after incubation. For the results of SEM and TEM, the bacterial membrane disruption of this E. coli was found in the PA-13-treated group when compared with the negative control. In conclusion, synthetic PA-13 with its antibacterial properties is an alternative antimicrobial peptide to antibiotics in the pig industry.